JURISDICTION OF THE EUROPEAN PUBLIC PROSECUTOR’S OFFICE - Bugarski, Tatjana; Pisarić, Milana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2020)
After many years of negotiations between the Member States and the institutions of the European Union, in October 2017, Regulation implementing enhanced cooperation on the establishment of the European Public Prosecutor’s Office was adopted. The subject of the paper is the presentation and critical analysis of certain solutions from the Regulation, which relate to the competence and scope of work of this supranational authority, in order to assess the possibilities for realizing its tasks in protecting the financial interests of the European Union.